Synthesis of a new thiourea derivative substituted 5,6-diamino-1,10-phenanthroline and crown ether and its complexes with Copper(II), Nickel(II) and Cobalt(II) - Elmali, F. T.; Avciata, U.; Demirhan, N.; Gul, A. (POLISH CHEMICAL SOC, 2007)
A new thiourea derivative ligand (LH2), 6-amino-5-ylamino-benzo[15-crown-5]-15-ylaminoethanethione[1,10]phenanthroline has been synthesized in the reaction of 5,6-diamino-1,10-phenanthroline with 15-isothiocyanatobenzo [15-crown-5] and its metal complexes with Cu(II), Ni(ll) and Co(ll) have been prepared. The structures and compositions of the ligand and the complexes have been confirmed by elemental analyses, UV-vis, FTIR, H-1 NMR (DMSO-d(6)), C-13 NMR (DMSO-d(6)), mass spectra (LC-MS) and magnetic measurements. The metal to the ligand ratio of the Cu(II), Ni(ll) and Co(ll) complexes have been found to be 1:2. Protonation constants of the ligand and overall formation constants of the complexes have been calculated from potentiometric data using the computer program.
Keywords: thiourea; crown ether; 1,10-phenanthroline; complexes; protonation constants; SCHIFF-BASE; SODIUM; Chemistry